Lupus nephritis following a streptococcal illness. (24th May 2012) - Yiallourides, M; Hussein, F; Rangaraj, S
Abstract : Presentation: This 15 year old boy with mild cerebral palsy (Right Hemiplegia) was referred with a history of cold and swollen hands and increasing athetoid movements of his left arm. While waiting to be seen and following a streptococcal like illness he presented to the renal team with frank haematuria, proteinuria and oedema. He had developed acute glomerulonephritis with a nephritic and nephrotic picture and a peak of Creatinine 224 umol/L. Investigations: Investigations showed low C3, C4 levels and raised ANA. Renal biopsy was undertaken which showed mesangiocapillary glomerulonephritis with glomerular deposition of IgG, IgM, IgA, C3 and C1q. All these features were consistent with lupus nephritis class IV. Diagnosis of Systemic Lupus Erythematosus: He fulfilled the American College of Rheumatology (ACR) criteria for a diagnosis of Systemic Lupus Erythematosus. On multisystem review, he did have Raynaud's phenomenon and a vasculitic rash over his palms. He was generally tired and had a disturbed sleep pattern. He had mild thrombocytopenia, lymphopenia and was dsDNA positive. An MRI did not show any evidence of central venous vasculitis. The athetoid movements were attributed to the Cerebral Palsy. Treatment: He was treated with pulsed intravenous Cyclophosphamide (initially two weekly and then monthly) and pulsed intravenous Methyl Prednisolone for 12 months. He was also commenced on Methotrexate which was continued after Cyclophosphamide. Other medications included Hydroxychloroquine and Aspirin. Penicillin was used at a prophylactic dose to prevent any recurrence of Streptococcal illness. The athetoid movements were treated with Carbamazepine. Progress: The complement protein levels normalised over the next few months and autoantibodies disappeared, including dsDNA. Eventually, all lupus disease modifying treatment was weaned off with him remaining well for over two years. He has recently developed persistent low-grade proteinuria and mild hypertension and has been commenced on Enalapril with good effect. The renal function remains normal with a GFR>120 ml/min/1.73m 2 . Conclusion: It is well recognised that infections can act as environmental triggers that induce or promote SLE. We have described a case of lupus with predominant renal involvement, presenting following a recent streptococcal illness. It is interesting to note the almost complete resolution of symptoms such as sometimes seen in drug- induced lupus.